2022
DOI: 10.1080/15476286.2022.2149170
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of piRNA sequences, targets and functions in nematodes

Abstract: Piwi proteins and Piwi-interacting RNAs (piRNAs) are best known for their roles in suppressing transposons and promoting fertility. Yet piRNA biogenesis and its mechanisms of action differ widely between distantly related species. To better understand the evolution of piRNAs, we characterized the piRNA pathway in C. briggsae , a sibling species of the model organism C. elegans . Our analyses define 25,883 piRNA producing-loci in C. briggsae .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…β–elimination was performed as described 54 . Small RNA-sequencing libraries were constructed following an previously established protocol 106 . Briefly, Small RNA samples were treated with the polyphosphatase PIR-1 to remove γ and β phosphates from 5′-triphosphorylated RNAs 107 .…”
Section: Methodsmentioning
confidence: 99%
“…β–elimination was performed as described 54 . Small RNA-sequencing libraries were constructed following an previously established protocol 106 . Briefly, Small RNA samples were treated with the polyphosphatase PIR-1 to remove γ and β phosphates from 5′-triphosphorylated RNAs 107 .…”
Section: Methodsmentioning
confidence: 99%
“…1c). The published C. briggsae piRNA high-throughput sequencing data 54 showed that, similar to that of C. elegans , piRNA genes located within clusters exhibited explicitly higher expression compared to those of out-cluster regions. The average expression level of clustered piRNAs bound to the PIWI protein was ∼50 RPM, while out-cluster piRNAs showed an average of ∼3.1 RPM (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To further test whether the clustering of piRNA genes is important for piRNA expression, we analyzed the distribution and expression of piRNAs in another nematode, C. briggsae . The C. briggsae genome contains over 25,000 piRNAs across 6 chromosomes 54 , clustering into one locus on LG Ⅰ and two loci on LG Ⅳ, which are termed Clusters 1, 2, and 3, respectively (Extended Data Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Mature piRNAs are commonly referred to as 21U-RNAs due to their strong propensity for a 5' uridine (U) and a primary length of 21-nucleotides (nts) (15)(16)(17)(18)(19). Type I and II piRNAs are found in C. elegans and its sibling species C. briggsae, with Type I piRNAs being notably much more abundant (16,20). Type I 21U-RNAs in C. elegans are encoded by over 15,000 individual mini-genes organized within two large clusters at Chromosome IV (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%